Exploring the Role of miRNA-9 and HLA-Class I Expression in Burn-Induced Vitiligo: The Interplay of Immune Response and Bacterial Infections - Hasan, Aya S.; Al-Rubaii, Bahaa Abdullah Laftaah (Iraqi Journal of Science, 2026)
Vitiligo is a complex autoimmune disorder characterized by the progressive loss of melanocytes, driven by a combination of genetic predisposition and immune dysfunction. This study explores the interaction between bacterial infections and immune activation in burn patients with vitiligo. Blood samples from 45 vitiligo patients and 45 burn patients were analyzed for HLA-class I and miRNA-9 expression using two-step qPCR, key regulators of immune response and melanocyte activity. Swabs from burn patients' skin ulcers were cultured to assess bacterial involvement in immune dysregulation. Results revealed significant immune imbalance, with HLA-class I overexpressed (fold change 29.98) and miRNA-9 downregulated (fold change 0.46), indicative of heightened immune activity. Bacterial cultures identified Pseudomonas aeruginosa (45.0%), Staphylococcus aureus (40.0%), and other species. HLA-class I upregulation was more pronounced in burn patients (95%) compared to vitiligo patients (65%), potentially linking inflammation or bacterial colonization to immune dysregulation. The findings suggest inflammation, potentially influenced by bacterial colonization, may exacerbate immune dysregulation and contribute to vitiligo onset, with miRNA-9 playing a regulatory role in the expression of HLA-ClassI.